Consequence of T Loop Morphology for Patients with Coronary Artery Stenosis - Kaminskiene, S.; Urbonaviciene, G.; Barauskienė, G.; Tamosiunaite, M.; Bluzaite, I. (Elektronika ir Elektrotechnika, 2004)
The aim of this study was to determine if T loop morphology variables are related to coronary artery stenosis. We assessed T loopmorphology parameters in 196 patients. In 126 patients coronary arteries stenoses ≥ 50% were determined. 70 patients normal coronaryarteries were determined. T loop morphology might reflect coronary artery stenosis: as the degree of coronary artery stenosis increases,T loop area and T loop index also increases: values of T loop area and T loop index were found to be higher in patients with coronaryartery stenosis ≥ 50 % (accordingly p=0.021 and p=0.011), for one vessel (accordingly 0.008 and p=0.031), three (accordingly p=0.045p=0.005) vessel diseases.T loop area and T loop index were higher in men with coronary artery stenosis ≥ 50 % (accordingly p=0.001and p=0.001). T loop morphology parameters did not differ significantly between damaged LAD, CX and RCA arteries. Ill.2, bibl. 5 (inEnglish; summaries in Lithuanian, English and Russian).